2022
DOI: 10.1111/jocd.14957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arginine glutamate (RE:pair) on wound healing and skin elasticity improvement after CO2 laser irradiation

Abstract: Background: Glutamic acid is known to be effective for keratinocyte proliferation, but its dermatological application is limited due to its poor solubility in water and various solvents.Aim: Here, the efficacy of the arginine glutamate ion pair (named as RE:pair) for recovering damaged skin and improving skin elasticity was investigated through the analysis of keratinocyte proliferation and collagen synthesis.Methods: Following the structural analysis of RE:pair using spectroscopic methods, a scratch assay, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In previous research, we have been conducting studies on the formation of IPs through intermolecular bonds (hydrogen bonds or dipole-dipole interactions) and their effects to (1) increase the solubility of poorly soluble substances, or (2) increase skin permeation efficacy. 26,27 As a synergistic effect verified by applying IP-BHA and magnolol together, MIC against C. acnes increased by 62.5 times and 2.5 times, respectively, compared to IP-BHA and magnolol alone. Along with a direct antibacterial effect, a necessary factor for bacterial inhibition is to reduce sebum secretion.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous research, we have been conducting studies on the formation of IPs through intermolecular bonds (hydrogen bonds or dipole-dipole interactions) and their effects to (1) increase the solubility of poorly soluble substances, or (2) increase skin permeation efficacy. 26,27 As a synergistic effect verified by applying IP-BHA and magnolol together, MIC against C. acnes increased by 62.5 times and 2.5 times, respectively, compared to IP-BHA and magnolol alone. Along with a direct antibacterial effect, a necessary factor for bacterial inhibition is to reduce sebum secretion.…”
Section: Discussionmentioning
confidence: 93%
“…The intermolecular bonding between salicylic acid and carnitine was analyzed through FT‐IR and absorbance spectra. In previous research, we have been conducting studies on the formation of IPs through intermolecular bonds (hydrogen bonds or dipole‐dipole interactions) and their effects to (1) increase the solubility of poorly soluble substances, or (2) increase skin permeation efficacy 26,27 . As a synergistic effect verified by applying IP‐BHA and magnolol together, MIC against C. acnes increased by 62.5 times and 2.5 times, respectively, compared to IP‐BHA and magnolol alone.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, glutamate has a low solubility in water [7.5 g/L (20 °C)], making it difficult to include it in high concentrations in cosmetics and moisture ointments. This formula overcomes the limitations by creating an emollient with ion pair of arginine and glutamate and increasing the skin permeability of both amino acids [19].…”
Section: Discussionmentioning
confidence: 99%
“…One prior study demonstrated the beneficial effects of arginine glutamate ion pair (known as RE:pair) on wound healing and enhancement of skin elasticity following CO2 laser irradiation. Glutamate, an ingredient in RE: pair, has been shown to promote keratinocyte proliferation [19]. In the skin, glutamate plays a vital role in metabolism and function, including collagen biosynthesis in fibroblasts [20].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this technology holds significant appeal for enhancing the efficient absorption and efficacy of cosmetic active ingredients. [18][19][20] In this study, we synthesized the Mandelic acid_Carnitine ion pairing complex (M_C complex) to develop a novel ingredient with effective exfoliating efficacy even under mildly acidic pH conditions (at pH 4.5) and characterized its structure using dynamic light scattering (DLS) and Fourier-transform infrared spectroscopy (FT-IR). The ion-pairing formation was confirmed through color changes in a simple solution.…”
Section: Introductionmentioning
confidence: 99%